2021
DOI: 10.3390/v13081631
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Immune Response to Vaccinia Virus LIVP Infection of BALB/c Mice and Protection against Lethal Reinfection with Cowpox Virus

Abstract: Mass vaccination has played a critical role in the global eradication of smallpox. Various vaccinia virus (VACV) strains, whose origin has not been clearly documented in most cases, have been used as live vaccines in different countries. These VACV strains differed in pathogenicity towards various laboratory animals and in reactogenicity exhibited upon vaccination of humans. In this work, we studied the development of humoral and cellular immune responses in BALB/c mice inoculated intranasally (i.n.) or intrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…This sampling date was chosen because we had previously demonstrated that the maximum peak of T cell-mediated immune response is reached on day 14 after the i.d. infection of BALB/c mice with the VACV LIVP [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This sampling date was chosen because we had previously demonstrated that the maximum peak of T cell-mediated immune response is reached on day 14 after the i.d. infection of BALB/c mice with the VACV LIVP [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Earlier, we revealed that the peak of the T cell-mediated immune response to infecting BALB/c mice with the LIVP virus is observed on day 14, while virus-specific IgG only start to be produced at this time; the IgG production reaches its maximum by day 28 [ 17 ]. Therefore, in this study, the level of T cell-mediated response of mice infected with VACV LIVP or its derivatives was assessed 14 days after the experiment had been started; the levels of IgM and IgG antibodies in these animals were analyzed on days 14 and 28.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FAdVs are double-stranded DNA viruses with a liner genome length of approximately 43-45 kb, highlighting its potential capacity to insert and deliver foreign genes, just like herpesviruses [27,28], poxviruses [29], and lentiviruses [30]. Mammalian adenoviruses have been developed into mature viral vectors, such as adenovirus-vectored Ebola and the recently emerging SARS-CoV-2 [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The assays were performed using the mouse IFN-γ ELISpot kit (R&D Systems, Inc., Minneapolis, MN, USA) according to the manufacturer’s instructions. The splenocytes were plated (100 μL/well) in duplicates 5 × 10 6 cells/mL and stimulated by a mixture of peptides (corresponding to VACV-specific BALB/c mice H2-d restricted epitopes): SPYAAGYDL, SPGAAGYDL, VGPSNSPTF, KYGRLFNEI, GFIRSLQTI, and KYMWCYSQV [ 18 ]. The pooled peptides (100 μL/well) were added at a concentration of 20 μg/mL for each peptide.…”
Section: Methodsmentioning
confidence: 99%